2009
DOI: 10.1121/1.3203210
|View full text |Cite
|
Sign up to set email alerts
|

Auditory stream segregation in cochlear implant listeners: Measures based on temporal discrimination and interleaved melody recognition

Abstract: The evidence that cochlear implant listeners routinely experience stream segregation is limited and equivocal. Streaming in these listeners was explored using tone sequences matched to the center frequencies of the implant's 22 electrodes. Experiment 1 measured temporal discrimination for short (ABA triplet) and longer (12 AB cycles) sequences (tone/silence durations = 60/40 ms). Tone A stimulated electrode 11; tone B stimulated one of 14 electrodes. On each trial, one sequence remained isochronous, and tone B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
56
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(64 citation statements)
references
References 29 publications
3
56
5
Order By: Relevance
“…Although both sequences resulted in increasing thresholds for increased electrode separation, build up is unlikely to occur for the shorter sequences (e.g. Bregman, 1978;Anstis and Saida, 1985), Cooper and Roberts (2009) argue that parallel performance for both sequences suggests that buildup is unlikely to be occurring for the longer sequences either, and therefore, the differences in rhythm detection thresholds were not likely due to stream segregation. Hong and Turner (2006) conducted a similar rhythm discrimination task using a short, three-tone sequence.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although both sequences resulted in increasing thresholds for increased electrode separation, build up is unlikely to occur for the shorter sequences (e.g. Bregman, 1978;Anstis and Saida, 1985), Cooper and Roberts (2009) argue that parallel performance for both sequences suggests that buildup is unlikely to be occurring for the longer sequences either, and therefore, the differences in rhythm detection thresholds were not likely due to stream segregation. Hong and Turner (2006) conducted a similar rhythm discrimination task using a short, three-tone sequence.…”
Section: Introductionmentioning
confidence: 94%
“…This type of perceptual instability is a common characteristic of stream segregation in normal hearing listeners (Anstis and Saida, 1985). Cooper and Roberts (2009) used a rhythm discrimination task to objectively investigate stream segregation. They found that increasing electrode separation led to rising rhythm detection thresholds.…”
Section: Introductionmentioning
confidence: 99%
“…Because of relatively poor pitch and timbre perception, CI users have difficulty in forming auditory streams. While some studies have shown that CI users can stream and segregate simple sequences using place and rate pitch cues (Chatterjee et al, 2006;Turner, 2006, 2009), others have shown that CI users cannot segregate auditory streams (Cooper and Roberts, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Data from NH listeners show that a sound's harmonic structure (both resolved and unresolved), defined by its F0, can be a good segregation cue in acoustic hearing (Assmann and Summerfield, 1990;Culling and Darwin, 1993). The brain can group together energy from resolved harmonics, which create a predictable pattern of excitation on the cochlea, to form one auditory object (a speakers voice for example) while ignoring energy from other frequency regions (e.g., background noise).…”
Section: Introductionmentioning
confidence: 99%
“…They found that CI users could stream amplitude modulated noise at relatively low frequencies and that the ability to stream pure tones was significantly correlated with speech perception in noise. Cooper and Roberts (2009) also investigate stream segregation in CI users and found that it was poor, even with a comparatively simple task. In NH subjects using CI simulation, Gaudrain et al (2008) showed that when F0 spectral cues were severely reduced, listeners may still make use of a weak F0 spectral cue to facilitate streaming.…”
Section: Introductionmentioning
confidence: 99%